1998
DOI: 10.1111/j.1530-0277.1998.tb05907.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption in Emergency Room Patients and the General Population: A Population‐Based Study

Abstract: Our purpose was to obtain epidemiological measures of the association between habitual alcohol consumption, alcohol consumption before the event and alcohol abuse/dependence, and emergency room (ER) attendance compared to the general population in Pachuca-Hidalgo, a city located in the central area of Mexico. The study was a population based case-control design. Data consisted of breath samples to estimated blood alcohol concentration, as well as an interviewer-administered questionnaire, collected on a 24-hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…This seems counterintuitive because it is known that alcoholics have an increased risk of injury. 20,42,43 Since patients with alcohol use disorders have a greater baseline risk for injury when compared with patients who do not have alcohol use disorders and because they drink more often, they will be at greater overall risk for injuries associated with drinking. While the chronic use of alcohol may lead to a higher risk of accident and injury, the acute effects of consuming alcohol among those who do not drink regularly, such as adolescents, may put an individual at greater short-term risk.…”
Section: Research Guilherme Borges Et Al Alcohol Use and Injuries Trmentioning
confidence: 99%
“…This seems counterintuitive because it is known that alcoholics have an increased risk of injury. 20,42,43 Since patients with alcohol use disorders have a greater baseline risk for injury when compared with patients who do not have alcohol use disorders and because they drink more often, they will be at greater overall risk for injuries associated with drinking. While the chronic use of alcohol may lead to a higher risk of accident and injury, the acute effects of consuming alcohol among those who do not drink regularly, such as adolescents, may put an individual at greater short-term risk.…”
Section: Research Guilherme Borges Et Al Alcohol Use and Injuries Trmentioning
confidence: 99%
“…legal limit for driving) [1][2][3]. Many emergency department studies and several meta-analyses have also concluded that exposure to alcohol substantially increases the risk of injury -particularly injuries occurring within 6 h of exposure to alcohol [4][5][6][7]. Based on agreement between BAC measurement and self-reported alcohol consumption, studies such as the WHO Collaborative Study Group on Alcohol and Injuries have defined alcohol-related injury as an injury with a positive self-report of alcohol consumption in the 6 h prior to the event [4].…”
Section: Introductionmentioning
confidence: 99%
“…These differences are likely reflected in the demographics of alcohol-related presentations to Bellevue. For instance, a similar urban hospital in Pachuca, Mexico reported 9.4 % of their a Patients with unspecified data were excluded from percentage calculations b Nonverbal intoxication refers to inebriated patients lacking a sufficient level of consciousness to speak c "Head CT anticipated" connotes that the treating physician intended to obtain a computerized tomography study of the patient's head, although we did not follow this to ensure that the CT order was actually executed ED patients to have used alcohol within 6 h of presentation, compared with an estimated 4.9 % of Bellevue patients who presented because of alcohol [17]. A recent survey of Tennessee urban EDs found a similar 4.9 % of presenting patients to be acutely intoxicated with alcohol based on serum analysis [7].…”
Section: Discussionmentioning
confidence: 99%